Sociology of Europeanization: volume 3 - Worschech, Susann; Eigmüller, Monika; Büttner, Sebastian (De Gruyter, 2022)
The numerous and far-reaching socio-political transformations that have taken place on the European continent since the mid-20th century have stipulated the emergence of new approaches and research fields in the social sciences. One of these is the development of a Sociology of Europeanization. This textbook provides an overview of its major topics, concepts, and research approaches. Each of the 14 chapters of this textbook introduces one particular topic of the Sociology of Europeanization ranging from major conceptual considerations to an exploration of the numerous spatial, cultural, economic, political, judicial, and socio-structural implications of Europeanization. Hence, this book is very suitable as a fundamental introductory reading and for teaching in European studies and related study programs. It is also recommended to everyone who is interested in more recent European history and current sociological studies of transnationalization. Concise and compact introduction into the state of art of the Sociology of Europeanization The book provides a clear-cut conception of the Sociology of Europeanization and of the dTvelopment of its major research areas Distinct didactical design
CRIS-Team Scopus Importer:2022-08-05
Keywords: European Borders; European Studies; Europeanization; Migration; Social Inequalities in Europe; Sociology of Europe; Transformation